Aramid fiber-epoxy composite material based on ultraviolet irradiation and preparation method thereof
The surface treatment of modified aramid fibers through ultraviolet radiation solves the problem of insufficient bonding between aramid fibers and epoxy resins, significantly improves the mechanical properties of the composite material, simplifies the modification steps, and reduces costs.
Patent Information
- Application Number
- CN202411636017.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, the interface bond between modified aramid fiber and epoxy resin is weak, which limits the mechanical properties of aramid enhancement of epoxy resin composite materials, and the modification steps are complex, high cost and poor modification effect.
The modified aramid fiber is surface treated by ultraviolet irradiation, increasing the surface roughness and introducing oxygen-containing functional groups, thereby improving its wettability and interface binding properties with epoxy resin.
The mechanical properties of aramid-epoxy composite materials are significantly improved, including bending, compression and torsional properties, and the modification steps are simplified, cost is reduced, and the modification effect is stable.
Smart Images

Figure CN119615604A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material engineering, and in particular to an aramid-epoxy composite material based on ultraviolet irradiation and a preparation method thereof. Background Art
[0002] Aramid fiber (PPTA), as a high-performance synthetic fiber, plays an important role in the field of composite materials due to its excellent mechanical properties and heat resistance, especially in engineering applications that require high strength and high modulus, such as insulating pull rods of GIS circuit breakers.
[0003] This material is well known for its high strength, high modulus, high temperature resistance, acid and alkali resistance, insulation and anti-aging properties. However, due to the high crystallinity of the surface of para-aramid fiber and the steric hindrance effect of the benzene ring, its surface is smooth and lacks sufficient active groups, resulting in weak interface bonding with epoxy resin, which limits the mechanical properties of aramid reinforced epoxy resin composites.
[0004] Although the existing surface modification technologies, such as plasma treatment, chemical oxidation and coating modification, can improve the interfacial bonding of aramid fibers to a certain extent, there are still problems such as complex processing, high cost or unstable modification effect. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an aramid-epoxy composite material based on ultraviolet irradiation and a preparation method thereof, so as to solve the problems of complex modification steps, high cost and poor modification effect in the prior art.
[0006] The technical solution of the present invention to solve the above technical problems is as follows:
[0007] The invention provides a method for preparing an aramid-epoxy composite material based on ultraviolet irradiation, wherein modified aramid is subjected to ultraviolet irradiation, and the irradiated modified aramid is mixed with epoxy resin to prepare the aramid-epoxy composite material.
[0008] Based on the above technical solution, the present invention can also be improved as follows.
[0009] Furthermore, the ultraviolet intensity of the ultraviolet irradiation is 50 μW / cm 2 The ultraviolet irradiation time is 10 to 40 minutes, and the wavelength is 100 nm to 280 nm.
[0010] Furthermore, the ultraviolet irradiation time is 20 minutes and the wavelength is 254 nm.
[0011] Furthermore, the modified aramid fiber is prepared by mixing aramid fiber with a modifier, ultrasonicating and drying to obtain the modified aramid fiber.
[0012] Furthermore, the modifier is an acetone solution.
[0013] Furthermore, the aramid fiber is poly(p-phenylene terephthalamide) fiber.
[0014] Furthermore, the irradiated modified aramid is mixed with epoxy resin, a curing agent is added, and then cured to obtain the aramid-epoxy composite material.
[0015] Furthermore, the mass fraction of the modified aramid fiber after irradiation is 50 to 80 parts, the mass fraction of the epoxy resin is 40 to 50 parts, and the mass fraction of the curing agent is 5 to 15 parts.
[0016] The present invention also provides an aramid-epoxy composite material based on ultraviolet irradiation, which is prepared by the above method.
[0017] The present invention also provides a method for testing the wettability enhancement of an aramid-epoxy composite material, which is tested in the preparation method as described above; the testing method comprises: after the ultraviolet irradiation, performing a surface property analysis on the modified aramid, performing an interlaminar shear test on the aramid-epoxy composite material, and obtaining a test result of the wettability enhancement of the aramid-epoxy composite material based on the results of the surface property analysis and the interlaminar shear test.
[0018] The beneficial effects of the present invention are:
[0019] (1) The method for preparing the aramid-epoxy composite material based on ultraviolet irradiation of the present invention, wherein ultraviolet irradiation can etch the fiber surface of the modified aramid fiber and increase the surface roughness;
[0020] (2) The method for preparing the aramid-epoxy composite material based on ultraviolet irradiation of the present invention can introduce oxygen-containing functional groups, thereby significantly improving the surface activity of the modified aramid and its wettability with epoxy resin, and enhancing the interface bonding performance;
[0021] (3) The preparation method of the aramid-epoxy composite material based on ultraviolet irradiation of the present invention can effectively improve the mechanical properties of the composite material;
[0022] (4) The method for preparing the aramid-epoxy composite material based on ultraviolet irradiation of the present invention has simple steps, low cost and stable modification effect;
[0023] (5) The aramid-epoxy composite material based on ultraviolet radiation of the present invention has good bending, compression and torsion resistance, and the interlaminar shear strength is significantly improved;
[0024] (6) The method for testing the wettability enhancement of the aramid-epoxy composite material of the present invention can effectively determine the wettability enhancement of the composite material by testing the material during the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The preparation method of the aramid-epoxy composite material based on ultraviolet irradiation of the present invention is a preparation and detection flow chart of Example 1;
[0026] Figure 2 The present invention is a method for preparing an aramid-epoxy composite material based on ultraviolet irradiation, and a schematic diagram of the principle of introducing oxygen-containing functional groups by ultraviolet irradiation;
[0027] Figure 3 The method for preparing the aramid-epoxy composite material based on ultraviolet irradiation of the present invention is as follows: in Example 2, infrared spectra of the surface of the modified aramid fiber under different ultraviolet irradiation times;
[0028] Figure 4 The method for preparing the aramid-epoxy composite material based on ultraviolet irradiation of the present invention, in Example 2, is a surface morphology of the modified aramid fiber that has not been irradiated with ultraviolet light;
[0029] Figure 5 The method for preparing the aramid-epoxy composite material based on ultraviolet irradiation of the present invention is as follows: in Example 2, the surface morphology of the modified aramid fiber with ultraviolet irradiation time of 5 minutes;
[0030] Figure 6 The method for preparing the aramid-epoxy composite material based on ultraviolet irradiation of the present invention is as follows: in Example 2, the surface morphology of the modified aramid fiber with ultraviolet irradiation time of 10 minutes;
[0031] Figure 7 The method for preparing the aramid-epoxy composite material based on ultraviolet irradiation of the present invention is a surface morphology image of the modified aramid fiber with ultraviolet irradiation time of 20 minutes in Example 2;
[0032] Figure 8 The method for preparing the aramid-epoxy composite material based on ultraviolet irradiation of the present invention is as follows: in Example 2, the surface morphology of the modified aramid fiber with ultraviolet irradiation time of 40 minutes;
[0033] Fig. 9 The present invention is a method for preparing an aramid-epoxy composite material based on ultraviolet irradiation. In Example 2, a comparison diagram of the contact angles of the modified aramid fiber and the epoxy resin under different ultraviolet irradiation times is shown;
[0034] Fig.10 The present invention is a method for preparing an aramid-epoxy composite material based on ultraviolet irradiation. In Example 2, a comparison chart of the interlaminar shear strength (ILSS) of composite materials prepared by using modified aramid fibers with different ultraviolet irradiation times is shown. DETAILED DESCRIPTION
[0035] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0036] The method for preparing the aramid-epoxy composite material based on ultraviolet irradiation of the present invention comprises the steps of subjecting modified aramid to ultraviolet irradiation, and mixing the irradiated modified aramid with epoxy resin to prepare the aramid-epoxy composite material.
[0037] The method for preparing the aramid-epoxy composite material based on ultraviolet irradiation of the present invention can etch the fiber surface of the modified aramid fiber and increase the surface roughness by breaking the molecular chain or inducing surface chemical reaction; at the same time, Figure 2 As shown, ultraviolet irradiation can also introduce oxygen-containing functional groups, such as carbonyl and hydroxyl, thereby significantly improving the surface activity of the modified aramid and its wettability with epoxy resin, enhancing the interface bonding performance, and improving the mechanical properties of the composite material.
[0038] The preparation method of the present invention improves the surface chemical activity and roughness of the aramid fiber, effectively improves the interfacial adhesion between the aramid fiber and the composite matrix, and enhances the interfacial force, which plays an important role in improving the mechanical properties of the aramid reinforced composite material. Compared with existing surface modification technologies such as plasma treatment, chemical oxidation and coating modification, the preparation method of the present invention has simple steps, low cost and stable modification effect.
[0039] Preferably, in the method for preparing the aramid-epoxy composite material based on ultraviolet irradiation of the present invention, the ultraviolet intensity of the ultraviolet irradiation is 50 μW / cm 2 The ultraviolet irradiation time is 10 to 40 minutes, and the wavelength is 100nm to 280nm.
[0040] Further preferably, the ultraviolet irradiation time is 20 minutes and the wavelength is 254 nm. With this ultraviolet irradiation time and wavelength, the surface roughness of the modified aramid fiber obtained is optimal and the contact angle is lowest, thereby making the interlaminar shear strength of the composite material optimal.
[0041] Preferably, the modified aramid is prepared by mixing aramid fiber with a modifier, ultrasonicating and drying to obtain the modified aramid.
[0042] Preferably, the modifying agent is an acetone solution.
[0043] Preferably, the aramid fiber is poly(p-phenylene terephthalamide) fiber, also known as para-aramid fiber. The ultraviolet irradiation of the present invention has a better modification effect on the para-aramid fiber, because the high crystallinity of the surface of the para-aramid fiber and the steric hindrance effect of the benzene ring make its surface smooth and lack sufficient active groups. After ultraviolet irradiation, the interface bonding between the para-aramid fiber and the epoxy resin is significantly enhanced, thereby significantly improving the mechanical properties of the obtained composite material.
[0044] Preferably, the irradiated modified aramid is mixed with epoxy resin, a curing agent is added, and then cured to obtain an aramid-epoxy composite material.
[0045] Preferably, the mass fraction of the modified aramid fiber after irradiation is 50 to 80 parts, the mass fraction of the epoxy resin is 40 to 50 parts, and the mass fraction of the curing agent is 5 to 15 parts.
[0046] The aramid-epoxy composite material based on ultraviolet irradiation of the present invention is prepared by the method as described above; the composite material of the present invention has good wettability after being mixed with epoxy resin because the surface roughness of the modified aramid is increased after ultraviolet irradiation, so that the obtained composite material has good mechanical properties.
[0047] The method for testing the wettability enhancement of the aramid-epoxy composite material of the present invention is tested in the preparation method as described above; the testing method comprises: after ultraviolet irradiation, performing surface property analysis on the modified aramid, performing interlaminar shear test on the aramid-epoxy composite material, and obtaining the test result of the wettability enhancement of the aramid-epoxy composite material according to the results of the surface property analysis and the interlaminar shear test.
[0048] Preferably, the surface characteristics analysis method is: using Fourier transform infrared spectrometer (FTIR) to analyze the chemical structure changes on the surface of the aramid fiber after irradiation, using scanning electron microscope (SEM) to observe the morphological changes on the surface of the aramid fiber after irradiation, and using energy dispersive X-ray spectrometer (EDX) to measure the surface element content of the aramid fiber at different modification times after irradiation.
[0049] The present invention is described below by means of specific examples.
[0050] Example 1 Preparation and testing of aramid-epoxy composite materials based on ultraviolet irradiation
[0051] This example adopts the preparation method and testing method of the present invention to obtain an aramid-epoxy composite material, and the specific steps are as follows:
[0052] Step 1: Prepare the modified aramid sample.
[0053] Specifically, a certain size of para-aramid (AF, 1414), 420 dtex, was cut and placed in a beaker containing an acetone solution. The beaker was cleaned in an ultrasonic cleaner for 2 hours and then placed in an oven for drying to obtain a modified aramid sample.
[0054] Step 2: Place the modified aramid sample obtained in step 1 on a UV irradiation treatment platform and set UV irradiation parameters.
[0055] Specifically, select a suitable UV irradiation device and set the irradiation intensity, time and wavelength to ensure that the irradiation device can evenly irradiate the entire surface of the aramid fiber sample.
[0056] The ultraviolet irradiation equipment used in this embodiment is an ultraviolet cross-linking instrument (Luyor-UCL-3500), the operating power is 230VAC 50 / 60Hz, and the ultraviolet lamp tube is 6×15W, which meets the ultraviolet irradiation requirements.
[0057] Set the UV intensity to 50 μW / cm 2 , aramid fibers were irradiated under UV light with a wavelength of 254nm.
[0058] Step 3: The modified aramid sample obtained in step 1 is subjected to ultraviolet irradiation treatment according to the ultraviolet irradiation parameters set in step 2.
[0059] Step 4: Analyze the surface characteristics of the modified aramid sample treated with UV radiation in step 3.
[0060] Fourier transform infrared spectrometer (FTIR) was used to analyze the chemical structure changes on the surface of aramid fiber after irradiation. The specific process was as follows: the aramid fiber sample after UV irradiation was placed on the sample stage, and the FTIR instrument was adjusted to the ATR total reflection mode with a range of 650-4000cm -1 , the number of scans is 64; start the instrument, let the infrared light irradiate the sample, the molecular groups absorb the infrared light of a specific frequency, and produce an absorption spectrum; analyze the interference pattern through computer software to obtain the infrared spectrum of the sample, so as to analyze the changes in the chemical structure, such as the appearance of new oxygen-containing functional groups.
[0061] A scanning electron microscope (SEM) was used to observe the morphological changes on the surface of the aramid fiber after irradiation. The specific process was as follows: the aramid fiber sample after UV irradiation was fixed on the sample stage of the SEM, and the sample was subjected to appropriate conductive spraying treatment to enhance signal detection; the acceleration voltage (10kv) and magnification (7x) of the SEM were adjusted to obtain the best surface morphology image; the SEM was used for scanning, and the electron beam excited secondary electrons and other signals during the scanning process of the sample surface; these signals were collected and amplified, converted into image signals, and finally the morphological features of the sample surface, such as surface roughness and cracks, were displayed on the display screen.
[0062] Energy dispersive X-ray spectrometer (EDX) was used to measure the surface element content of aramid fiber at different modification times after irradiation. The specific process was as follows: the aramid fiber sample after UV irradiation was placed on the sample stage of EDX, and the sample surface was ensured to be flat and clean; the aramid fiber surface mainly contained three elements: C, O, and N. In order to characterize the modification effect, the EDAXOctane Super EDX detector was used, which integrated a backscattered electron (BSE) detector and used energy dispersive X-ray spectroscopy (EDX) to analyze the elemental composition of the aramid fiber surface, such as carbon (C), oxygen (O), and nitrogen (N).
[0063] Step 5: Mix the modified aramid sample obtained in step 3 after UV irradiation with epoxy resin to prepare a composite material.
[0064] Specifically, the aramid fiber treated with ultraviolet radiation is uniformly mixed with epoxy resin, the mixture is poured into a mold, and cured under certain conditions to form a composite material.
[0065] The mass ratio of the aramid fiber treated with UV radiation to the epoxy resin is 1:1, and the curing condition is 90°C.
[0066] Step 6: Conduct mechanical property testing and interface failure analysis on the composite material obtained in step 5.
[0067] The specific method is to conduct interlaminar shear test on the composite material, obtain and record the interlaminar shear strength of the fiber reinforced epoxy composite interface, and evaluate the effect of ultraviolet radiation treatment on the mechanical properties of the composite material.
[0068] After mechanical loading, the failure of the composite interface was observed using a microscope. The effect of UV irradiation on the failure of the composite interface was analyzed.
[0069] Step 7: Record and analyze the data obtained in the above steps to obtain the result of whether the wettability of aramid-epoxy is enhanced.
[0070] Specifically, all experimental data were recorded, including irradiation parameters, surface characteristics analysis results, wettability test results, mechanical properties test results, and interface failure analysis results. Statistical software was used for data analysis, and based on the surface characteristics of the aramid fiber and the mechanical properties of the composite material obtained before and after UV irradiation, it was determined whether the wettability of the aramid-epoxy was enhanced.
[0071] Example 2 Comparison of the effects of different UV irradiation times
[0072] This example adopts the method of Example 1 to examine the performance of the composite material obtained at external irradiation times of 0 min, 5 min, 10 min, 20 min and 40 min, respectively.
[0073] The infrared spectra of each sample are shown in Figure 3 The morphological characteristics of the surface of each sample are shown in Figures 4 to 8 The surface element contents of each sample are shown in Table 1.
[0074] Table 1
[0075]
[0076] The aramid fibers treated with ultraviolet radiation are mixed with epoxy resin to prepare a composite material.
[0077] like Fig. 9 As shown, when the aramid fiber treated with UV radiation comes into contact with the epoxy resin matrix, the resin penetrates the fiber surface more fully and the aramid-epoxy contact angle is significantly reduced compared with the aramid fiber that has not been treated with UV radiation.
[0078] In addition, the composite materials prepared by aramid fibers treated with ultraviolet radiation have greatly reduced failure at the interface when subjected to mechanical loads, and the bending, compression and torsional properties of the composite materials are significantly enhanced.
[0079] Interlaminar shear tests were performed on each composite material, and after mechanical loading, the failure at the composite material interface was observed using a microscope. Fig.10 It can be seen that the interlaminar shear strength of the composite material prepared by using aramid fiber treated by UV radiation is significantly improved, and the mechanical properties of the composite material with UV irradiation time of 20 minutes are the best.
[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an aramid-epoxy composite material based on ultraviolet irradiation, characterized in that: The modified aramid is subjected to ultraviolet irradiation, and the irradiated modified aramid is mixed with epoxy resin to prepare an aramid-epoxy composite material.
2. The method for preparing an aramid-epoxy composite material based on ultraviolet irradiation according to claim 1, characterized in that: The ultraviolet intensity of the ultraviolet irradiation is 50 μW / cm 2 The ultraviolet irradiation time is 10 to 40 minutes, and the wavelength is 100 nm to 280 nm.
3. The method for preparing an aramid-epoxy composite material based on ultraviolet irradiation according to claim 2, characterized in that: The ultraviolet irradiation time is 20 minutes, and the wavelength is 254 nm.
4. The method for preparing an aramid-epoxy composite material based on ultraviolet irradiation according to claim 1, characterized in that: The modified aramid is prepared by mixing aramid fiber with a modifier, ultrasonicating and drying to obtain the modified aramid.
5. The method for preparing an aramid-epoxy composite material based on ultraviolet irradiation according to claim 4, characterized in that: The modifier is an acetone solution.
6. The method for preparing an aramid-epoxy composite material based on ultraviolet irradiation according to claim 4, characterized in that: The aramid fiber is poly(p-phenylene terephthalamide) fiber.
7. The method for preparing an aramid-epoxy composite material based on ultraviolet irradiation according to any one of claims 1 to 6, characterized in that: The irradiated modified aramid is mixed with epoxy resin, a curing agent is added, and then cured to obtain the aramid-epoxy composite material.
8. The method for preparing an aramid-epoxy composite material based on ultraviolet irradiation according to claim 7, characterized in that: The mass fraction of the modified aramid fiber after irradiation is 50 to 80 parts, the mass fraction of the epoxy resin is 40 to 50 parts, and the mass fraction of the curing agent is 5 to 15 parts.
9. An aramid-epoxy composite material based on ultraviolet radiation, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
10. A method for testing the wettability enhancement of aramid-epoxy composite materials, characterized in that: The test is carried out in the preparation method as described in any one of claims 1 to 8; the test method comprises: after the ultraviolet irradiation, performing a surface property analysis on the modified aramid, performing an interlaminar shear test on the aramid-epoxy composite material, and obtaining a test result of the wettability enhancement of the aramid-epoxy composite material based on the result of the surface property analysis and the result of the interlaminar shear test.
Citation Information
Patent Citations
Aramid fiber (AF) surface modification method, product and preparation method of product
CN105986465A
Method for preparing polyester fiber reinforced epoxy composite material based on ultraviolet radiation modification
CN106317786A
Preparation method for partially-flexible stabproof composite material for civil use
CN108467569A
Resin composition for preparing aramid fiber composite core by pultrusion process
CN112048151A
Preparation process and application of phthalonitrile modified aramid fiber
CN116837621A